Quality estimation the of maximum-likelihood algorithm to the task of space distribution of elements by PIXE - Kovalchuk, I.K.; Levenets, V.V.; Shchur, A.O. (Вопросы атомной науки и техники, 2008)
The numerical research is carried out for different approximations of likelihood-function and Fisher's matrix
with reference to maximum-likelihood algorithm at determination of impurity profile of certain chemical element in
researched sample by PIXE. It is shown, that the testing of this algorithm, previously led, points to a basic opportunity
of its application for restoration of impurity profile by PIXE. However, its practical application causes difficulties,
and the expression offered earlier for likelihood-function does not allow determining accuracy of restoration of
impurity profile. The problems preventing from opportunity of practical use of algorithm are studied. Проведено численне дослідження для різних наближень функції правдоподібності и матриці Фішера при застосуванні до алгоритму максимальної правдоподібності при визначенні профілю домішку якогось хімічного елемента в зразку, що досліджується методом PIXE. Показано, що проведене раніше тестування цього алгоритму вказує на принципову можливість його використання для встановлення профілю домішки методом PIXE, однак, його практичне використання визиває труднощі, а наведений раніше вираз для функції правдоподібності не дозволяє визначити точність встановлення профілю домішки. Досліджені проблеми, що перешкоджають можливому практичному використанню алгоритму. Проведено численное исследование для разных приближений функции правдоподобия и матрицы Фишера применительно к алгоритму максимального правдоподобия для определения профиля примеси некоторого химического элемента
в исследуемом образце методом PIXE. Показано, что проведенное ранее тестирование этого алгоритма указывает на
принципиальную возможность его применения для восстановления профиля примеси методом PIXE, однако, его практическое применение вызывает трудности, а предложенное ранее выражение для функции правдоподобия не позволяет
определить точность восстановления профиля примеси. Изучены проблемы, препятствующие возможности практического использования алгоритма.